‘Sermo de sepulchro Domini’: un estudio sobre los folios 3v y 4r del manuscrito ‘BM ms. 528’ de Cambrai - Pascua Vílchez, Fidel (Romanitas - Revista de Estudos Grecolatinos, 2020)
Study on folios 3v and 4r of manuscript BM ms. 528 of Cambrai, containing a Latin text of an unknown author, titled Sermo de sepulchro dñi. Based on Godoi (2014), Quetglás (2006) and Sánchez Prieto (2015), among others, we analyze the subject of study by comparing it to the digital collections of Documenta Catholica Omnia and Corpus Corporum, pursuing the following objectives: to transcript the folios content into Word format, to explain the external and internal organization of the text, to identify the author of the sermon, to provide a translation to Spanish. We conclude that: the text is unedited until now; during its transcription, the copyist made three errors of omission due to the pronunciation at internal dictation and to the misreading of an abbreviation; the external organization of the text doesn’t match the internal one; it is not possible to establish the identity of the author.
Keywords: Liber sancti Andreae de castello; Illuminated Codex of XII Century; Medieval Latin Philology; Homiliary